ERFVII transcription factors and their role in the adaptation to hypoxia in Arabidopsis and crops - Loreti, Elena; Perata, Pierdomenico (Frontiers in Genetics, 2023)
In this review, we focus on ethylene transcription factors (ERFs), which are a crucial family of transcription factors that regulate plant development and stress responses. ERFVII transcription factors have been identified and studied in several crop species, including rice, wheat, maize, barley, and soybean. These transcription factors are known to be involved in regulating the plant's response to low oxygen stress -hypoxia and could thus improve crop yields under suboptimal growing conditions. In rice (Oryza sativa) several ERFVII genes have been identified and characterized, including SUBMERGENCE 1A (SUB1A), which enables rice to tolerate submergence. The SUB1A gene was used in the development of SUB1 rice varieties, which are now widely grown in flood-prone areas and have been shown to improve yields and farmer livelihoods. The oxygen sensor in plants was discovered using the model plant Arabidopsis. The mechanism is based on the destabilization of ERFVII protein via the N-degron pathway under aerobic conditions. During hypoxia, the stabilized ERFVIIs translocate to the nucleus where they activate the transcription of hypoxia-responsive genes (HRGs).In summary, the identification and characterization of ERFVII transcription factors and their mechanism of action could lead to the development of new crop varieties with improved tolerance to low oxygen stress, which could have important implications for global food security.